2021
DOI: 10.2166/wst.2021.143
|View full text |Cite
|
Sign up to set email alerts
|

Performance of polycaprolactone/TiO2 composite membrane for the effective treatment of dairy effluents

Abstract: This work aims the utilisation of Polycaprolactone (PCL) based membrane for the treatment of dairy wastewater for the first time to the best of our knowledge. PCL is a biodegradable polymer with high biocompatibility and good oil resistance. The chlorine tolerance analysis of PCL based membrane exhibited a good tolerance against chlorine. The PCL/TiO2 nanocomposite membrane with the addition of Polyethylene glycol (PEG) was prepared and tested for protein separation. The dependency of contact angle with time w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In another example, nanofibrous membranes made of chitosan and PCL delivered a composite architecture inheriting the antimicrobial properties of chitosan in combination with the advantageous characteristics of PCL [ 23 ]. In another example, hybrid nanocomposite membranes of PCL/TiO 2 were investigated for the treatment of wastewater from the dairy industry, showing that such membranes could combine the hydrophobic properties and chlorine resistance of PCL with the antibacterial and anti-fouling properties associated with the hydrophilicity of titanium dioxide [ 24 ]. Finally, our group also investigated several composite electrospun systems based on PCL, such as the PCL/Ag endowed with a Ag nanocoating of PCL fibers via magnetron sputtering [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another example, nanofibrous membranes made of chitosan and PCL delivered a composite architecture inheriting the antimicrobial properties of chitosan in combination with the advantageous characteristics of PCL [ 23 ]. In another example, hybrid nanocomposite membranes of PCL/TiO 2 were investigated for the treatment of wastewater from the dairy industry, showing that such membranes could combine the hydrophobic properties and chlorine resistance of PCL with the antibacterial and anti-fouling properties associated with the hydrophilicity of titanium dioxide [ 24 ]. Finally, our group also investigated several composite electrospun systems based on PCL, such as the PCL/Ag endowed with a Ag nanocoating of PCL fibers via magnetron sputtering [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Maio et al showed that graphene oxide-decorated polycaprolactone membranes possessed sorption capacity of phenol molecules on its nanosurfaces, and can offer a cost-effective approach for water treatment [35]. Meanwhile, Nivedita et al prepared polyethylene glycol tailored PCL/TiO 2 nanocomposites, which can effectively filter proteins in effluents from the dairy industry [36].…”
Section: Introductionmentioning
confidence: 99%